Trastorno bipolar con comorbilidad física y mental en población adulta - Vega Rivilla, Angella Anahy (2023)
Bipolar disorder corresponds to a severe mental disorder associated with high rates of morbidity, mortality and suicide. In general terms, comorbidity increases the complexity of the disease burden and significantly influences the clinical picture, course and outcome of the pathology; for this reason, the following study was proposed as an objective, document the most frequent comorbidities in this disorder focusing on the adult population. To achieve this objective, a quantitative bibliographic review was carried out, with a non-experimental and longitudinal, descriptive design, based on a population of 2,746 scientific articles from the databases SciElo, PubMed, Google Scholar, Base. The investigative process was supported by the PRISMA 2020 declaration. The sample of 30 scientific articles published between 2000 and 2019, was selected and statistically analyzed, corresponding to 9,813 adults with a diagnosis of bipolar disorder. 59.6% of the sample belongs to the female gender, 44.2% represents ages between 30 and 40 years, 40.5% are of North American origin (United States and Canada), 54.2% have some illness additional comorbid, with substance use disorders at 37.4% and anxiety disorders at 21.2%, the most common comorbidities of bipolar disorder; On the other hand, cardiometabolic alterations with 6.4% are the most prevalent physical diseases. Based on the results, we conclude the importance of identifying the various comorbidities within bipolar disorder in order to promote adequate intervention and treatment